The Mechanical and Thermal Properties of Cement CAST Mortar/Graphene Oxide Composites Materials - Thidatip Janjaroen; Sunisar Khammahong; Wattana Tuichai; Attaphol Karaphun; Chaiwat Phrompet; Chaval Sriwong; Chesta Ruttanapun (International Journal of Concrete Structures and Materials, 2022)
Abstract This paper presents the influence of the graphene oxide (GO) sheet contents at conditions of 0, 0.01, 0.03, 0.05, and 0.1 wt% on the mechanical and thermal properties of GO/CAST 11 LW mortar (GMT) composites for heat insulating brick. The GMT composites were prepared by a simple mixing method. The structure of GMT composites was investigated by X-ray diffraction (XRD) and Raman spectroscopy (Raman) techniques. The small grain sizes of GMT composites were confirmed by transmission electron microscopy (TEM). The mechanical properties of GMT composites are increased with increasing GO contents. A lot of functional groups in GO such as carboxylic acid reacted with a calcium silicate hydrate, CaH 2 O 4 Si (CSH), calcium hydroxide, Ca(OH) 2 (CH) and Ettringite, and Ca 6 [Al(OH) 6 ] 2 (SO 4 ) 3 ·26H 2 O (CA) phases in the mortar, which can be considered good mechanical properties in the GMT composites. The heat insulation values of GMT composites were improved by the interaction with the CSH, CH, and CA phases in the cement mortar on the surface of GO. The highest compressive and tensile strengths and low heat transfer rate of about 0.465 W/min were observed at 0.05 of GO (GMT_0.05) composites in the curing age of 7 days. Thus, a new pathway of GMT composites can be prepared by a simple mixing method to significantly improve the mechanical and thermal properties of mortar GMT composites.
Keywords: Concrete and Cement Materials Research; Magnesium Oxide Properties and Applications; Graphene research and applications